LEGAL REVIEW OF COMBAT MEDIC SERVICES IN HANDLING GUNSHOT WOUNDS OF BRIMOB PERSONNEL IN OPERATIONAL DUTIES IN PAPUA - Baginda Zulfikar; Muhammad Arif Sahlepi; Marice Simamarta (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze combat medic services in handling gunshot wounds sustained by Brimob personnel during operations in Papua, with a focus on the legal basis, operational effectiveness, and challenges encountered. The research employs a normative juridical method with a document study approach and analysis of legislation, including Law No. 17 of 2023, Government Regulation No. 28 of 2024, Police Chief Regulations (Perkap), Police Regulations (Perpol), as well as the Standard Operating Procedures (SOP) and Tactical Combat Casualty Care (TCCC) protocols implemented in Brimob units. The results indicate that combat medic services have a strong legal foundation and clear technical standards; however, their effectiveness is influenced by multidimensional obstacles such as geographical conditions, logistical limitations, personnel competency, and the absence of comprehensive regulations regarding tactical medical authority. This study recommends improving internal regulations, enhancing tactical-medical training capacity, strengthening logistics, and conducting regular legal evaluations to ensure patient rights are fulfilled, service effectiveness is increased, and legal risks for personnel are minimized.